Harmony of Inter-Religious Communication in the History of Perangtopat Ritual - Suhadah, Suhadah; Rohmah, Nurliya Ni'matul (Universitas Muhammadiyah Mataram, 2023)
This study relates the history of perangtopat (the rice cake war) which is a cultural ritual of the Muslims and Hindus in Lombok Island, Indonesia. Through a literature study, in depth interviews and observation this research has revealed that the history of the perangtopat ritual cannot be seperated from the life story of DatuMilir, an Islamic Leader who was an Islamic Missionary and who is credited with the emergence of a spring which is now known as Kemaliq. The perangtopat ritual which is centered at Kemaliq began as an expression of pleasure by the people of Lingsar Village at the emergence of the spring. They showed their pleasure by throwing food at each other. The ritual is still maintained until now even though it has undergone slight modifications; such as the change of sacrificial animal from a cow to a water buffalo at the request of King Karangasem (Hindu) who ruled Lombok until 1759. In this modern era the perangtopat ritual has experienced further modification to include artistic and entertainment aspects. These changes that have been incorporated reflect a sense of tolerance by the Muslims in Lingsar District, West Lombok Regency, Indonesia.